Framework of informal specification validation with visual specification and human factor involvement to improve requirement specification quality - Fauziah, Zainuddin (2019)
Requirement engineering has attracted a great deal of attention from researchers and practitioners in recent years. Researchers endeavor in software engineering had identified that failure and deficiency of software system often rooted to requirement specification undertaken. Previous studies indicate that there are issues in human factor involvement especially in validating informal specification. Such phenomena would later cause serious impacts to quality of informal specification such as incompleteness, incorrectness, ambiguity, difficult to verify and incomprehensible. In practice, informal specification is preferred by practitioners to perform documentation for system requirement compared to semi- or formal specification. In contrast, current research scenario shown more studies were conducted for semi- or formal specification validation; whereby, visualization technique was successfully adopted in assisting human factor for validation purposes.Apparently, informal specification validation using the same technique is not yet explored; and obviously visualization is able to give similar impact to informal specification quality as it does for semi– and formal specification validation. Consequently, to transform text into visual, the process required systematic assistance to specify ‘‘what’’ to be visualized and ‘‘how’’ to visualize them. Therefore, this study addresses these issues by proposing a framework of informal specification validation that includes communication medium (visualization) and direct human factor involvement in satisfying the intended specification quality attributes (with respect to human factor perspective). The study starts with identifying the nature of how human factor influencesthe requirement engineering process, levels of specification language validated by practitioners, current mechanisms in assisting human factor, recent specification language in validation perspective and identifying quality attributes for requirement specification that are significant to human factor involvement using Systematic Literature Reviewapproach. Based on the findings, a conceptual framework was developed. Transformation procedure in the proposed framework was then formulated to assist the transformation from text to visual. Finally, this study adopts mix-methods (explanatory sequential) for framework validation purposes that include case studies and expert review. Putting The Three Dimensions of Requirements Engineering framework and the Software Visualization Taxonomy as the basis, the Requirement Specification with Human Factor Validation (REsHFv) framework was proposed to deal with informal specification validation by human factor involvement using visualization as the medium in order to achieve complete, correct, unambiguous, comprehensible and verifiable informal specification. From the validation assessment, the framework was proven to be applicable and was able to produce good quality of informal specification for a project, the percentage of the quality improvement is between 55% to 30% for each quality attributes. The t-Test (from the case study) for paired two-sample (Software Requirement Specification - SRS total marks) for mean p-value for this test is less than 0.05 (p <0.05). Hence, this implies that there is a significant evidence to conclude that the SRS quality constructed with Software Visual Specification (SVS) is able to provide improved quality of SRS at 5% significance level. Meanwhile, experts reviewed that the results indicatethe proposed framework is applicable and relevant in real software engineering setting.This research contributes to the development framework for quality informal specification by incorporating human factor and software visual specification for informal specification validation purposes. Thus, the proposed REsHFv framework is expected to provide beneficial impact to the quality of informal specification resulted from direct human factor involvement during specification validation.